Cell Membrane-Coated Biomimetic Nanocarriers for Plaque-Targeted Atherosclerosis Therapy: Molecular Mechanisms, Inflammatory Microenvironments, and Translational Challenges - Ruiyu Zhang; Xujing Yuan; Jinpeng Sun; Yumiao Wei (International Journal of Molecular Sciences, 2026)
Atherosclerosis (AS) is a lipid-driven chronic inflammatory disease and the principal pathological basis of coronary artery disease, ischemic stroke, and peripheral artery disease. Despite advances in lipid-lowering, antiplatelet, anti-inflammatory, and revascularization strategies, current treatments do not selectively modulate the heterogeneous cellular and inflammatory microenvironments within individual plaques. Cell membrane-coated nanoparticles (CMNs) have therefore emerged as biomimetic delivery platforms that combine the functional versatility of synthetic nanocores with selected biological properties of donor-cell membranes. This review summarizes the fabrication of CMNs and critically compares platelet-, macrophage-, neutrophil-, monocyte-, erythrocyte-, and hybrid membrane-coated nanoplatforms, together with emerging T-cell-targeted nanotherapeutic strategies. Particular attention is given to membrane-source selection, receptor–ligand interactions, immune evasion, lesion-directed accumulation, stimulus-responsive cargo release, and the modulation of inflammation, oxidative stress, lipid metabolism, and defective efferocytosis. We further discuss major translational barriers, including donor- and activation-state-dependent membrane heterogeneity, incomplete or unstable coating, manufacturing reproducibility, scalability, thrombogenicity, immunogenicity, and the limited predictive value of short-term small-animal models. A pathology-matched and minimum-sufficient-complexity framework is proposed to guide the rational development of safer, more reproducible, and clinically relevant biomimetic nanotherapies for AS.